1978
DOI: 10.1111/j.1365-2125.1978.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of isoprenaline‐induced plasma cyclic AMP response by aminophylline in normal and asthmatic subjects.

Abstract: 1The effect of intravenous aminophylline infusion (6mg-1 kg in 20 min, then 0.9 mg-' kg-' h thereafter) and its interaction with inhaled isoprenaline (800 1tg ex inhaler) on plasma cyclic AMP levels was studied in five normal and five asthmatic subjects. 2 Aminophylline infusion alone did not significantly change plasma cyclic AMP levels in either group.3 In both groups, the plasma cyclic AMP response to isoprenaline aerosol inhalation was enhanced by aminophylline, although to a lesser degree in the asthmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…However, if the /-receptor is stimulated significantly, such as by the upright posture, then this amplification is clinically evident. This explanation fits well with data showing potentiation of the rise in plasma cAMP seen with isoprenaline inhalation by theophylline although theophylline alone caused no significant elevation of plasma cAMP (Trembath & Shaw, 1978). It may also explain why theophylline fails to bronchodilate normal resting subjects (Estenne et al, 1980) but is a very effective bronchodilator in acutely ill patients (Piafsky et al, 1975;Senior et al, 1975) who presumably have a greater level of sympathetic activity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, if the /-receptor is stimulated significantly, such as by the upright posture, then this amplification is clinically evident. This explanation fits well with data showing potentiation of the rise in plasma cAMP seen with isoprenaline inhalation by theophylline although theophylline alone caused no significant elevation of plasma cAMP (Trembath & Shaw, 1978). It may also explain why theophylline fails to bronchodilate normal resting subjects (Estenne et al, 1980) but is a very effective bronchodilator in acutely ill patients (Piafsky et al, 1975;Senior et al, 1975) who presumably have a greater level of sympathetic activity.…”
Section: Discussionsupporting
confidence: 77%
“…However, this was shown with concentrations of theophylline of approximately 200 mg/l and it has therefore been suggested that the therapeutic concentration of free theophylline in plasma (approximately 10-20 mg/l) is insufficient to inhibit phosphodiesterase in vivo (Horrobin et al, 1977;Polson et al, 1978). This is confirmed by the failure to show a significant change in plasma cyclic AMP following theophylline administration in normal subjects (Jones et al, 1979;Parrott et al, 1976;Trembath & Shaw, 1978). Alternative mechanisms of action have therefore been proposed such as modulation of prostaglandin metabolism (Vinegar et al, 1976), blockade of adenosine receptors (Fredholm & Sydbom, 1980), increased secretion of adrenaline by the adrenal medulla (Atuk et al, 1967) and alteration of intracellular calcium (Brisson et al, 1972).…”
Section: Introductionmentioning
confidence: 98%
“…Its possible interaction with f2-adrenoceptor agonists has not yet been fully explored either at molecular level (Miech & Lohman, 1975;Trembath & Shaw, 1978) or in patients with airways narrowing. Conventional doses have been shown to have some additive effect when combined in asthmatics (Campbell, Middleton, Mackenzie, Shetter, McHardy & Kay, 1976;Wolfe, Tashkin, Calvarese & Simmons, 1978;Marlin, Hartnett & Berend, 1978) but these studies are incomplete since they ignore both individual differences in response and in theophylline clearance.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Furthermore, other potent PDE inhibitors such as dipyridamole [58-32-2] are not bronchodilators (73). Finally, although clinical studies have shown that neither po nor continuous iv theophylline has a direct effect on circulating cyclic AMP levels (74,75), one study has shown that iv theophylline significant potentiates the increase in cyclic AMP levels induced by isoproterenol (74).…”
Section: Xanthine Derivativesmentioning
confidence: 99%